2013
DOI: 10.1371/journal.pone.0056694
|View full text |Cite
|
Sign up to set email alerts
|

De novo Transcriptome Sequencing Reveals a Considerable Bias in the Incidence of Simple Sequence Repeats towards the Downstream of ‘Pre-miRNAs’ of Black Pepper

Abstract: Next generation sequencing has an advantageon transformational development of species with limited available sequence data as it helps to decode the genome and transcriptome. We carried out the de novo sequencing using illuminaHiSeq™ 2000 to generate the first leaf transcriptome of black pepper (Piper nigrum L.), an important spice variety native to South India and also grown in other tropical regions. Despite the economic and biochemical importance of pepper, a scientifically rigorous study at the molecular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…Two conserved miRNAs (miR166 and miR171) were identified using experimental in silico approach from black pepper ). In addition, a (CT) dinucleotide SSR in the hairpin precursors of miRNA (Joy and Soniya 2012) and potential microsatellite derived miRNAs (Joy et al 2013) were identified from black pepper. In this paper, we report the first small RNA profiling using Illumina high-throughput sequencing for the comprehensive investigation of miRNAs of black pepper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two conserved miRNAs (miR166 and miR171) were identified using experimental in silico approach from black pepper ). In addition, a (CT) dinucleotide SSR in the hairpin precursors of miRNA (Joy and Soniya 2012) and potential microsatellite derived miRNAs (Joy et al 2013) were identified from black pepper. In this paper, we report the first small RNA profiling using Illumina high-throughput sequencing for the comprehensive investigation of miRNAs of black pepper.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report the first small RNA profiling using Illumina high-throughput sequencing for the comprehensive investigation of miRNAs of black pepper. The secondary stem-loop precursors of conserved and novel miRNAs were identified from recently sequenced black pepper mRNA transcriptome data (Joy et al 2013). Expression pattern of eight conserved miRNAs were verified and potential targets of majority of the miRNAs were predicted.…”
Section: Introductionmentioning
confidence: 99%
“…This reflects that SSRs loci in R. glutinosa obviously prefer to particular category of genes. Additionally, 35 SSRs were found to locate in non-coding transcripts, in who's derived SSRs a bias of base composition was obviously observed, that was also found in other animals and plants Joy et al, 2013;Asadi and Monfared, 2014). It was reported that EST-SSR markers were identified on transcribed regions of DNA that were often considered as putative functional sequences (Jiang et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…KEGG database enables to understand biological functions of genes with the Pathway annotation. The KEGG pathway database records networks of molecular interactions in the cells, and variants of them specifi c to particular organisms (Kanehisa et al 2010 ;Joy et al 2013 ).…”
Section: Functional Classifi Cation Of Unigenes By Clusters Of Ortholmentioning
confidence: 99%